Star Wars. Hyperspace stories. the Bad Batch : ghost agents - Moreci, Michael (Dark Horse Books, 2025)
"A daring heist strikes at the heart of the Republic war effort! What has been stollen? A list of Republic ghost agents, whose covert actions across the galaxy provide vital information to the Jedi and their allies. The Bad Batch are called upon to recover the missing list and bring the thief to justice. Easier said than done! Their mission takes Hunter, Wrecker, Crosshair, and Tech to the seediest corners of the galaxy"-- Provided by publisher.